Pertumbuhan Duddingtonia flagrans pada Air Liur, Larutan Rumen, Blok Komin, dan Agar Semen - Zainuddin Ahmad, Riza; -, Beriajaya (Jurnal Veteriner; Vol 11 No 1 (2010), 2010)
Duddingtonia flagrans is selected nematophagous fungi as biological control to nematode worm. Theaim of this research was to show that the survival of in vitro tested to D. flagrans mold growth is effectedby artificial saliva, rumen fluid, enzymes and agar-cement and comin block applicator. The testing wasdone two steps : Firstly the conidia’s was multicated and the secondly the growth of D.flagrans tested insaliva, rumen fluid and comin block, agar cement applicator. The result showed that mold could surviveand grow in condition such as in gastrointestinal fluid of sheep and in comin block and in agar-cementapplicator (1 and 2%). It can be concluded that D. flagrans could grow in medium containing rumen fluid,saliva, enzymes and comin block and agar-cement applicator.
Keywords: Comin block, agar-cement, Duddingtonia flagrans, saliva, rumen fluidRazak Achmad